Analysis of the Relationship Between Dietary Patterns and the Risk of Non-Communicable Diseases Among Urban Adolescents in Mataram City, Lombok - Saputra, Lalu Hendra (Lembaga Publikasi Ilmiah Nusantara, 2025)
Non-communicable diseases (NCDs), including obesity, diabetes, and hypertension, are becoming increasingly prevalent among adolescents, especially in urban areas experiencing rapid lifestyle changes. This study aims to analyze the relationship between dietary patterns and the risk of NCDs among adolescents in Mataram City, Lombok. A cross-sectional study was conducted involving 300 high school students aged 15–18 years from five schools across Mataram. Data collection included validated food frequency questionnaires (FFQ), anthropometric measurements, and structured interviews to assess lifestyle factors. Dietary patterns were classified into three categories: healthy (high intake of fruits, vegetables, and whole grains), mixed (moderate intake of processed and sugary foods), and unhealthy (frequent consumption of fast food, sweetened beverages, and high-fat snacks). Risk indicators such as Body Mass Index (BMI), blood pressure, and family history of NCDs were analyzed using chi-square tests and logistic regression. The results indicated a significant association between unhealthy dietary patterns and elevated BMI (p < 0.01) and increased systolic blood pressure (p < 0.05). Adolescents with unhealthy eating habits were found to be 2.7 times more likely to be at risk for NCDs compared to their peers with healthy diets (OR = 2.7; 95% CI: 1.7–4.3). These findings emphasize the urgent need for targeted nutritional education and health promotion strategies in urban schools within Mataram. Early interventions can play a crucial role in reducing the long-term burden of NCDs among the youth population.